2012
DOI: 10.3174/ajnr.a3148
|View full text |Cite
|
Sign up to set email alerts
|

Robust Perfusion Deficits in Cognitively Impaired Patients with Secondary-Progressive Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:Cognitive impairment is a common, disabling symptom of MS. We investigated the impact of cerebral perfusion and brain and lesion volumetry on cognitive performance in 45 patients with SPMS by using MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…From a clinical point of view, reduced white and gray matter CBF in patients with MS has thus far been associated with cognitive manifestations, [67][68][69][70] which are remarkably similar to those described in ischemic leukoencephalopathy. 71 One study found that reduced deep gray matter perfusion in MS negatively correlated with fatigue, 72 which is a very common but poorly understood cause of impaired activities of daily living in patients with MS.…”
Section: Role Of Reduced Cbf In Ms Pathology?mentioning
confidence: 90%
“…From a clinical point of view, reduced white and gray matter CBF in patients with MS has thus far been associated with cognitive manifestations, [67][68][69][70] which are remarkably similar to those described in ischemic leukoencephalopathy. 71 One study found that reduced deep gray matter perfusion in MS negatively correlated with fatigue, 72 which is a very common but poorly understood cause of impaired activities of daily living in patients with MS.…”
Section: Role Of Reduced Cbf In Ms Pathology?mentioning
confidence: 90%
“…17 The skeletonized FA maps were compared between patients with and without cognitive impairment using FSL's Randomise tool, which conducts permutation-based nonparametric testing while correcting for multiple comparisons across space. 26 To be conservative and assumption free, voxelwise group analysis was conducted with 5000 permutations and threshold-free cluster enhancement (p corr Ͻ .05).…”
Section: Statistical and Image Analysismentioning
confidence: 99%
“…17 Briefly, regions of GM and WM were delineated algorithmically, and T2-weighted hyperintensities and T1-weighted hypointensities were hand traced using Medical Image Processing, Analysis, and Visualization version 4.0 (National Institutes of Health, Bethesda, Maryland). The FMRIB Software Library (FSL, http:// www.fmrib.ox.ac.uk/fsl) processed the DTI scans.…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion is supported by various pathological and imaging studies 8, 2224 which have shown that cGM lesions may develop prior to the appearance of WM plaques 22 , arise independently of, and are poorly correlated with T2h-l formation 23,24 . A number of pathological and imaging papers have increasingly implicated an independent etiology for cGM lesion formation attributed either to the direct presence of meningeal-derived neurotoxic substances or secondary microglial activation mediated through meningeal/supbial inflammation and manifest as a gradient of demyelination centered upon the subpial cortex 24, 27 .…”
Section: Discussionmentioning
confidence: 99%